Predictive Modeling of Thoracic Radiotherapy Toxicity and the Potential Role of Serum Alpha-2-Macroglobulin - von Reibnitz, Donata; Yorke, Ellen D.; Oh, Jung Hun; Apte, Aditya P.; Yang, Jie; Pham, Hai; Thor, Maria; Wu, Abraham J.; Fleisher, Martin; Gelb, Emily; Deasy, Joseph O.; Rimner, Andreas (Frontiers in Oncology, 2020)
Background To investigate the impact of alpha-2-macroglobulin (A2M), a suspected intrinsic radioprotectant, on radiation pneumonitis and esophagitis using multifactorial predictive models. Materials/methods Baseline A2M levels were obtained for 258 patients prior to thoracic radiotherapy (RT). Dose-volume characteristics were extracted from treatment plans. Spearman’s correlation (Rs) test was used to correlate clinical and dosimetric variables with toxicities. Toxicity prediction models were built using least absolute shrinkage and selection operator (LASSO) logistic regression on 1000 bootstrapped datasets. Results Grade ≥2 esophagitis and pneumonitis developed in 61 (23.6%) and 36 (14.0%) patients, respectively. The median A2M level was 191 mg/dL (range: 94-511). Never/former/current smoker status was 47 (18.2%)/179 (69.4%)/32 (12.4%). We found a significant negative univariate correlation between baseline A2M levels and esophagitis (Rs=-0.18/p=0.003) and between A2M and smoking status (Rs=0.13/p=0.04). Further significant parameters for grade ≥2 esophagitis included age (Rs=-0.32/p<0.0001), chemotherapy use (Rs=0.56/p<0.0001), dose per fraction (Rs=-0.57/p<0.0001), total dose (Rs=0.35/p<0.0001), and several other dosimetric variables with Rs>0.5 (p<0.0001). The only significant non-dosimetric parameter for grade ≥2 pneumonitis was sex (Rs=-0.32/p=0.037) with higher risk for women. For pneumonitis D15 (lung) (Rs=0.19/p=0.006) and D45 (heart) (Rs=0.16/p=0.016) had the highest correlation. LASSO models applied on the validation data were statistically significant and resulted in areas under the receiver operating characteristic curve of 0.84 (esophagitis) and 0.78 (pneumonitis). Multivariate predictive models did not require A2M to reach maximum predictive power. Conclusion This is the first study showing a likely association of higher baseline A2M values with lower risk of radiation esophagitis and with smoking status. However, the baseline A2M level was not a significant risk factor for radiation pneumonitis.